2010
DOI: 10.1037/a0019285
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms linking socioeconomic status to smoking cessation: A structural equation modeling approach.

Abstract: Objective-Although there has been a socioeconomic gradient in smoking prevalence, cessation, and disease burden for decades, these disparities have become even more pronounced over time.The aim of the current study was to develop and test a conceptual model of the mechanisms linking socioeconomic status (SES) to smoking cessation.Design-The conceptual model was evaluated using a latent variable modeling approach in a sample of 424 smokers seeking treatment (34% African American; 33% Latino; 33% White). Hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
162
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(181 citation statements)
references
References 89 publications
15
162
3
1
Order By: Relevance
“…Thus, the purpose of the current study was to examine parameters (i.e., trajectory and volatility) of prequit variables that may be linked to smoking abstinence on the quit date among a sample of homeless smokers undergoing an aided quit attempt. Based on conceptual models describing the links between socioeconomic disadvantage and health (e.g., Businelle et al, 2010;Kendzor et al, 2009;Matthews & Gallo, 2011) as well as prior EMA research among domiciled smokers (e.g., Piasecki et al, 2002;Shiffman & Waters, 2004;Wetter et al, 2011), it was hypothesized that EMA measures of motivation for quitting, positive coping expectancies, positive smoking expectancies, quit self-efficacy, smoking urges, negative affect, positive affect, restlessness, hostility, and stress in the week prior to the quit date would influence quit date abstinence.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the purpose of the current study was to examine parameters (i.e., trajectory and volatility) of prequit variables that may be linked to smoking abstinence on the quit date among a sample of homeless smokers undergoing an aided quit attempt. Based on conceptual models describing the links between socioeconomic disadvantage and health (e.g., Businelle et al, 2010;Kendzor et al, 2009;Matthews & Gallo, 2011) as well as prior EMA research among domiciled smokers (e.g., Piasecki et al, 2002;Shiffman & Waters, 2004;Wetter et al, 2011), it was hypothesized that EMA measures of motivation for quitting, positive coping expectancies, positive smoking expectancies, quit self-efficacy, smoking urges, negative affect, positive affect, restlessness, hostility, and stress in the week prior to the quit date would influence quit date abstinence.…”
Section: Introductionmentioning
confidence: 99%
“…Trait hostility consistently predicts higher smoking rates in both men and women (Lipkus et al, 1994;Siegler et al, 1992;Whiteman et al, 1997). In contrast to the large number of studies focusing on the association between maternal depression/ stress and smoking during pregnancy (Bullock et al, 2001;Businelle et al, 2010;Cinciripini et al, 2010;Ludman et al, 2000;Munafò et al, 2008;Reitzel et al, 2010), few investigated anger, hostility, or aggression among pregnant smokers. One exception is the study by Schuetze et al (2008), which indicated that pregnant smokers report higher hostile mood and maternal hostility.…”
mentioning
confidence: 99%
“…18 Consequently, certain factors such as perceived stress, economic stress, biomarkers of stress all are more likely to cause the relapse. 12,[19][20][21] Those with any one support person who was part of their tobacco cessation program had higher cessation rates than those who had no support person, which was assessed at 3, 6 and 12 months. It was higher with men, and women showed no effect with respect to long term abstinence.…”
Section: Impact Of Social Support On Tobacco Cessationmentioning
confidence: 99%